Pitting Corrosion of Steinmann Stainless Steel Pins in Simulated Body Fluid Using Cyclic Polarization Technique - Santos, Stephanie; Mena, Manolo (Philippine Engineering Journal, 2020)
Abstract – Locally available Steinmann stainless steel pins were subjected to cyclic voltammetry in Kokubo simulated body fluid after immersion in SBF from 0 to 7 days.  Results showed that the pins were susceptible to pitting corrosion from Day 0, with the degree of pitting increasing with the length of immersion.  This may be due to the degradation of the initial passivation on the steel by SBF solution.  SEM EDX analysis showed the presence of chloride precipitates in the pitting area.  Chloride is known to induce autocatalytic corrosion of stainless steels.  Optical Emission Spectroscopic analysis of the samples showed that one sample is  SS304 and the other two were  SS316L.  The SS304 pins showed a higher tendency towards pitting corrosion when compared with the SS316L pins.    Keywords – Steinmann pins, pitting corrosion, cyclic polarization